The Small Non-coding Vault RNA1-1 Acts as a Riboregulator of Autophagy - Horos, R; Büscher, M; Kleinendorst, R; Alleaume, A-M; Tarafder, AK; Schwarzl, T; Dziuba, D; Tischer, C; Zielonka, EM; Adak, A; Castello, A; Huber, W; et al. (Cell Press, 2019)
Vault RNAs (vtRNA) are small non-coding RNAs transcribed by RNA polymerase III found in many eukaryotes. Although they have been linked to drug resistance, apoptosis, and viral replication, their molecular functions remain unclear. Here, we show that vault RNAs directly bind the autophagy receptor sequestosome-1/p62 in human and murine cells. Overexpression of human vtRNA1-1 inhibits, while its antisense LNA-mediated knockdown enhances p62-dependent autophagy. Starvation of cells reduces the steady-state and p62-bound levels of vault RNA1-1 and induces autophagy. Mechanistically, p62 mutants that fail to bind vtRNAs display increased p62 homo-oligomerization and augmented interaction with autophagic effectors. Thus, vtRNA1-1 directly regulates selective autophagy by binding p62 and interference with oligomerization, a critical step of p62 function. Our data uncover a striking example of the potential of RNA to control protein functions directly, as previously recognized for protein-protein interactions and post-translational modifications.